Hubungan Pengetahuan, Sikap Dengan Perilaku Pengaturan Diet Hipertensi Di Puskesmas Guntur Garut - Iwan Shalahuddin; Udin Rosidin; Umar Sumarna (Politeknik Negeri Jember, 2021)
Hypertension is a non-communicable disease in which cases are still many in Indonesia. Hypertension diet is one of the treatments to prevent recurrence in hypertension. The knowledge of attitude and behaviuor in a person will be carried out with proper management. Knowledge is something that can underlie or encourage someone to take action or behaviuor. The recommended hypertension diet for people with hypertension is the consumption of food that is low in salt, low in fat, increase fibre, increase potassium intake, do not consume cigarette, coffee and alcohol, increase consumption of vegetable and fruit. The purpose of this research was to determine the description of knowledge, attitude and behavior of hypertension sufferers about dietary food regulation in the working area of Guntur Health Center Garut. This research was conducted using a quantitative approach. The population in this research were all hypertension sufferers in Guntur Health Center as many as 265 people. The sample in this research amounted to 159 people using accidental sampling techniques. the instrument used in the form of a questionnaire, which includes: knowledge, attitude and behaviour. Data analysis used univariate analysis. The result of this research indicated that the majority of respondents had a good level of knowledge as many as 152 people (95,6%),159 people (100%) had a supportive attitude, and 159 people (100%) had positive behavior. There is a relationship between knowledge and attitudes towards dietary regulation behavior for hypertensive patients with analytical test results obtained p-value less than 0.05 (knowledge 0.033 and attitude 0.013). From the result of this research, there were several behaviours that had to be improved and had to be maintained. like reducing the consumption of full cream milk, biscuit and egg yolk and maintaining consumption of fruit, vegetable and food that contain low fat.The result of this research expected to be used as a reference and learning both in the provision of health education or other nursing care for the knowledge, attitude and behaviour of hypertension sufferers about dietary food regulation